VITAMIN D SUPPLEMENTATION DECREASES THE BODY FAT STORES AND PLASMA OXIDATIVE STRESS OF OBESE RATS (Arquivos do Mudi, 2023)
The study aimed to verify the effects of vitamin D3 (cholecalciferol) supplementation on thebody fat composition and plasmatic oxidative stress of obese rats. The 21 days old maleWistar rats were acclimatized in the sectorial animal breed until they were 30 days old(CEUA nº 5866200720). Then the obesity induction was initiated using the cafeteria diet(Western Diet; WD). The animals were divided into 2 groups: CTL, rats fed a normal diet;WD, animals fed a WD. After 90 days old, they were subdivided into two other groups: CTL-VD and WD-VD, which received vitamin D3 during 40 days (5.600 UI/week by gavage). At130 days old, blood was collected and the plasma separated for the oxidative stress assays.After, body fat deposits were collected, separated and weighed. The adiposity index of WDrats were higher than CTL and WD-VD animals. The epididymal, retroperitoneal andmesenteric fat deposits of WD were respectively 30%, 46% and 50% higher in WD rats whencompared to WD-VD rats. Body weight gain and abdominal fat were also decreased inanimals supplemented with vitamin D3. Regarding the oxidative stress parameters in theplasma, the levels of carbonyl protein groups were lower, and protein thiol groups and totalantioxidant capacity (TAC) were higher in WD rats when compared to the CTL and WD-VDgroups. In conclusion, treatment with VD3 was able to reduce both fat stores and the levels ofoxidative stress markers in the plasma of rats with cafeteria diet-induced obesity.